2018
DOI: 10.1002/glia.23523
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic brain injury‐induced neuronal damage in the somatosensory cortex causes formation of rod‐shaped microglia that promote astrogliosis and persistent neuroinflammation

Abstract: Microglia undergo dynamic structural and transcriptional changes during the immune response to traumatic brain injury (TBI). For example, TBI causes microglia to form rod‐shaped trains in the cerebral cortex, but their contribution to inflammation and pathophysiology is unclear. The purpose of this study was to determine the origin and alignment of rod microglia and to determine the role of microglia in propagating persistent cortical inflammation. Here, diffuse TBI in mice was modeled by midline fluid percuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
119
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(142 citation statements)
references
References 56 publications
15
119
5
Order By: Relevance
“…Although previous data regarding the effects of microglial depletion on acute GFAP changes after TBI are conflicting (Witcher et al, 2018), we did not observe significant changes in GFAP expression or morphology at chronic timepoints after TBI. Reported differences of PLX5622 treatment on posttraumatic astrocyte reactivity may reflect differences in the injury model (midline fluid percussion vs controlled cortical injury), time-points examined (3 days vs 3 months post-injury), or the treatment paradigm employed (pre-treatment vs late posttrauma treatment).…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Although previous data regarding the effects of microglial depletion on acute GFAP changes after TBI are conflicting (Witcher et al, 2018), we did not observe significant changes in GFAP expression or morphology at chronic timepoints after TBI. Reported differences of PLX5622 treatment on posttraumatic astrocyte reactivity may reflect differences in the injury model (midline fluid percussion vs controlled cortical injury), time-points examined (3 days vs 3 months post-injury), or the treatment paradigm employed (pre-treatment vs late posttrauma treatment).…”
Section: Discussioncontrasting
confidence: 97%
“…Reported differences of PLX5622 treatment on posttraumatic astrocyte reactivity may reflect differences in the injury model (midline fluid percussion vs controlled cortical injury), time-points examined (3 days vs 3 months post-injury), or the treatment paradigm employed (pre-treatment vs late posttrauma treatment). In addition, Witcher et al reported that depletion of microglia prior to TBI did not alter injury-induced neuronal injury in the cortex at 7 days post-injury (Witcher et al, 2018). In contrast, our study demonstrates that delayed depletion of microglia during the chronic stages of TBI significantly reduce neuronal cell loss in cortex and hippocampus.…”
Section: Discussioncontrasting
confidence: 73%
“…Neuroinflammation and gliosis can often persist for months or even years post-brain trauma [8,10,53,55]. The physiological processes involved in prolonging the inflammatory state of the TBI brain remain poorly defined.…”
Section: Discussionmentioning
confidence: 99%
“…To explore how pre-existing meningeal lymphatic dysfunction influences neuroinflammation in TBI we first investigated changes in GFAP and Iba1 staining, as aggravated gliosis often correlates with worsened clinical outcomes in TBI [49][50][51][52][53]. We found that possessing defects in the meningeal lymphatic system before TBI (TBI+Visudyne+laser) results in greater distance covered by GFAPexpressing astrocytes surrounding the lesion site at 24 hrs post-injury (Figure 3e,f).…”
Section: Meningeal Lymphatic Dysfunction Predisposes the Brain To Examentioning
confidence: 99%
“…The period of post-TBI is divided into 3 phases: an acute phase, a subacute phase, and a chronic phase. Generally, the acute phase is the first 7 days after TBI, the subacute phase is between 7 days and 3 weeks after TBI, and the chronic phase begins 3 to 5 weeks after TBI [2][3][4][5]. To date, the majority of pre-clinical studies have focused on pharmaceutical interventions in neuroprotection in the acute phase of TBI, such as complement inhibition [6], immunomodulation [7], angiotensin II receptor blockage [8], and cerebral infusion of insulin-like growth factor-1 [9].…”
Section: Introductionmentioning
confidence: 99%